Emotional intelligence, servant leadership, and development goal orientation in athletic directors. Issue 3 (June 2019) - Lee, Ye Hoon
Highlights: This study focuses on the off-the-court sport leaders (i.e., athletic directors). This study examines methods by which athletic directors pursue development goals. Emotional intelligence positively predicts servant leadership style. Servant leadership positively predicts development goal orientation. Servant leadership plays a mediating role in the proposed relationship. Abstract: Scholars and policy makers have long considered sport as a vehicle for promoting young athletes' well-being, educational experience, and citizenship skills. Athletic directors can play a significant role in this process by establishing organizational goals that can foster the development of young athletes and also by ensuring that other personnel abide by these goals. However, little is known about methods athletic directors can use to focus on such development goals in the midst of the current winning-at-all-costs culture surrounding sports. Thus, the purpose of this study is to examine the relationships between emotional intelligence, servant leadership, and development goal orientation among high school athletic directors. A total of 445 athletic directors located in 48 states in the United States completed an online survey. The results indicated that emotional intelligence is positively associated with servant leadership, which in turn is positively associated with development goal orientation. The mediation analysis also revealed that servant leadership fully mediates the relationship between emotional intelligence and development goal orientation among athletic directors. The findings of this research assist in understanding how sports governing bodies can educate athletic directors to initiate development-oriented reform of the winning-at-all-costs culture in sports.